Debt load impact on sustainable development of Russian regions - Yu. S. Lisachkina (Вестник университета)
The paper assesses the level of debt load on sustainable and effective development of the Russian regions under the conditions of sanctions, restrictions, and unstable economic situation. The authors of the study faced the following tasks: to conduct a comparative assessment of regional sustainable development and debt load, to consider the directions for effective management of the load as an element of economic security of the constituent entities, as well as to analyze the economic essence and peculiarities of formation of the Russian regions’ public debt. Various approaches of theoretical and practical plan to the study of the subject of the research have been evaluated and used. The methods and techniques that inﬂuence the level of debt load on sustainable development of the constituent entities through the use and application of various innovative technologies, methods, techniques, etc. at the current stage of economic development of the country have been considered and evaluated. The conducted research results can be applied when developing effective directions to reduce the debt load as a factor that affects the regional sustainable development.